2015
DOI: 10.1097/sle.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of the Early Outcomes of Open and Laparoscopic Surgery of Liver Hydatid Cyst

Abstract: Laparoscopic surgery seems to be effective and safe, with low morbidity rates for uncomplicated cysts in accessible segments of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In a comparative study, 73 patients with uncomplicated LH were assigned to either group of laparoscopic or open surgery, and were followed for approximately 18 months. Biliary fistula, cyst cavity infection and wound infection were not different between the two groups (evidence type 2b) . Finally, one systematic review of nonrandomized studies regarding the treatment of complicated LH is worthy of note.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparative study, 73 patients with uncomplicated LH were assigned to either group of laparoscopic or open surgery, and were followed for approximately 18 months. Biliary fistula, cyst cavity infection and wound infection were not different between the two groups (evidence type 2b) . Finally, one systematic review of nonrandomized studies regarding the treatment of complicated LH is worthy of note.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 301 records were recovered, 47 of which fulfilled the selection criteria: three SR, three CT, five cohorts studies, 24 case series and 12 not classifiable OS . The studies had a level of evidence of 1b, 2a, 2b, 3a and 4 of prognostic and therapy scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that the recurrence rate of hepatic hydatid after primary surgery is 6% to 30%, and there is no significant difference in postoperative complications between laparoscopic surgery and open surgery [ 15 ]. However, open surgery is still the main surgical treatment at present, and more and more studies hope to achieve therapeutic purposes with more minimally invasive methods, such as perforator-grinder-aspirator-apparatus (PGAA) and nanosecond pulsed electric field (nsPEF).…”
Section: Discussionmentioning
confidence: 99%
“…However, published literature has shown comparable recurrence rates. [ 5 6 7 8 14 15 16 ] Laparoscopic surgery should be tailored to prevent any spillage. Palanivelu et al .…”
Section: Discussionmentioning
confidence: 99%